2014
DOI: 10.1542/peds.2014-1027
|View full text |Cite
|
Sign up to set email alerts
|

Functional Status in Children With ADHD at Age 6–8: A Controlled Community Study

Abstract: WHAT'S KNOWN ON THIS SUBJECT: Children who have attentiondeficit/hyperactivity disorder (ADHD) attending clinical services have poorer outcomes in adolescence on a range of measures. However, it is unknown how early in development these impairments appear, particularly for community-ascertained samples.WHAT THIS STUDY ADDS: At age 6 to 8 years, children in the community with ADHD have significantly poorer mental health, academic performance and social function compared with control children. Children who have … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
51
0
1

Year Published

2015
2015
2018
2018

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 58 publications
(55 citation statements)
references
References 39 publications
3
51
0
1
Order By: Relevance
“…Although previous research has found an association between parental mental health and irritability [37], we found little evidence of an association between parent mental health and DMDD status in our study. In the current sample, children with ADHD had parents with poorer mental health compared to non-ADHD controls [17]. Thus, it may be that DMDD does not add to the burden experienced by these already impaired families.…”
Section: Discussionmentioning
confidence: 65%
See 2 more Smart Citations
“…Although previous research has found an association between parental mental health and irritability [37], we found little evidence of an association between parent mental health and DMDD status in our study. In the current sample, children with ADHD had parents with poorer mental health compared to non-ADHD controls [17]. Thus, it may be that DMDD does not add to the burden experienced by these already impaired families.…”
Section: Discussionmentioning
confidence: 65%
“…To date, only one study has examined the prevalence of DMDD in children with ADHD. In a community-based study of children aged 6-8 years, 21.8 % of children with ADHD met criteria for DMDD in comparison to 1.4 % of non-ADHD controls [17]. The correlates of DMDD in children with ADHD have yet to be examined.…”
Section: Dmdd In Children With Adhdmentioning
confidence: 99%
See 1 more Smart Citation
“…It was notable that almost 40% of parents had not received professional help for their child, despite their child meeting diagnostic criteria for ADHD. We have demonstrated that by age 7 these children were already experiencing major impairments in academic, social and emotional functioning compared with controls,21 so parents had cause to be concerned. The reasons why a substantial minority of parents of children with ADHD do not seek professional help for their children warrants further investigation.…”
Section: Discussionmentioning
confidence: 84%
“…O impacto que as manifestações comportamentais de crianças com TDAH têm sobre os ambientes geralmente difere. Nesse sentido, o relato de pessoas que convivem com a criança nos diferentes contextos é essencial para uma avaliação global dos aspectos comportamentais necessários para a definição de queixas relativas ao TDAH (Alexander & Liljequist, 2016;Efron et al, 2014;Kotte, Faraone, & Biederman, 2013;Willcutt et al, 2013;Whitehouse, Robinson, & Zubrick, 2011).…”
unclassified